Smart Tree on Knowledge of The Process of Calculus in elementary school children - Putri, Rifa Fauziah Syaifia; Amelia, Nanda Riska; Sulistiani, Silvia (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: According to Riskesdas 2018, it was also found that Indonesian people have not brushed their teeth routinely and correctly. The percentage of people who brush their teeth every day and at the right time is still low. Research purposes: Understanding how to use Smart Tree in gaining an understanding of the calculus process in grade V students of MI Hibrul Ulama. Methods : This study uses a survey method with quasi experimental method approach involving pre test and post test design, the sample in this study amounted to 28 respondents. The data analysis of this study uses the Bivariate Test, namely the Normality Test and the Wilcoxon Test. Result : Statistical tests show that there is an increase between the pre-test and post-test, which is indicated by an asymp.sig value of 0.000 on the knowledge variable, meaning that the variable is <0.05 so that Ha can be accepted. Conclusion : the influence of smart tree media toincrease knowledge of dental and oral health in the process of calculus in class V students of MI Hibrul Ulama Bogor.